Educational and Skills Mismatches: Unravelling Their Effects on Wages Across Europe - Loredana Cultrera; Benoît Mahy; François Rycx; Guillaume Vermeylen (Global Labor Organization (GLO), 2022)
This paper is among the firsts to investigate the impact of overeducation and overskilling on workers' wages using a unique pan-European database covering twenty-eight countries for the year 2014, namely the CEDEFOP's European Skills and Jobs (ESJ) survey. Overall, the results suggest a wage penalty associated with overeducation. When interacting educational mismatch with skills mismatch into apparent overeducation and genuine overeducation, the results suggest that the highest wage penalty is reached for workers that are both overeducated and overskilled.
Keywords: J21; J24; 330; Educational mismatch; Skills mismatch; Wages; European survey